Exploring materials creative design for everyday objects - Alesina, Inna 1969-; Lupton, Ellen (New York Princeton Architectural Press, 2010)
This book is an action-oriented, accessible guide to design thinking that addresses both the how and why of product design. It encourages designers to look beyond the abstraction of pure forms or the whimsy of virtual objects, and instead to make and test real objects in a studio environment.--[book cover]
Unlock ideas: using materials for inspiration -- Study, prototype, test: journey through the design process -- Know your values: why design? -- Think with materials: everyday uses and inspiring experiments -- Make it real: from prototype to product.
Includes bibliographical references (page 206) and index.
FA-2707g donated by Stanley Ruiz.
Keywords: Materials; Industrial design